IMPLEMENTATION OF THE CITY WITHOUT SLUMS (KOTAKU) PROGRAM IN THE SERVICES OF PUBLIC WORKS AND PEOPLE'S SETTLEMENTS (PUPR) SIDOARJO REGEN IMPLEMENTASI PROGRAM KOTA TANPA KUMUH (KOTAKU) DI DINAS PEKERJAAN UMUM DAN PERMUKIMAN RAKYAT (PUPR) KABUPATEN SIDOARJO - Novellita Myrsa Puspatiara Putri; Suci Megawati (Universitas Negeri Surabaya, 2022)
Having a healthy environment is everyone's right. In this case, the state is also responsible for this. However, slum areas are still a social problem that has not yet been resolved. It is recorded that in 2021, Sidoarjo Regency has 276.26 hectares of slum areas spread over 52 villages. In response to this, the Public Housing and Settlement Service Office of Sidoarjo Regency implemented the Slum-Free City Program in tackling slum areas. The Kotaku Program is a community-based infrastructure repair activity program whose main goal is to tackle slum areas. The purpose of this study is to see how the implementation and results of the Kotaku Program at the PUPR Office of Sidaorjo Regency are. The theory used in this study uses the public policy implementation model by Mulyadi (2015:12). This research approach uses a qualitative descriptive approach that will be carried out in Sidoarjo Regency. The result of this research is that the implementation of the Kotaku Program carried out by the PUPR Service has gone quite well by fulfilling every stage starting from the preparation stage, implementation stage, and completion stage. It was recorded that in 2021, 19 of the 52 villages targeted to become slum areas have been overcome and can reduce flooding and reduce slum areas in Sidoarjo Regency. This program can also help overcome unemployment due to the impact of Covid-19 by increasing the income of people who are heads of families who have lost their jobs so that it can reduce the unemployment rate that previously soared in Sidoarjo Regency. In addition, the implementation of this program will also carry out gradual evaluation monitoring both from activities and from implementing agencies so that in the future it becomes an effort to improve policies that are better and optimal.